(untitled) (Orfeu, 2025)
This article outlines a methodological, technical, and poetic trajectory structured around three main axes: collaborative vector-based composition, the development of a graphic-proportional notation system for xenharmonic intervals, and acoustic modeling through FFT convolution. These processes converge in the album Hybris: Ocarinas do Mestre Nado, released by the independent label Seminal Records as a phonographic synthesis of the research. Developed within the Gambioluteria research group (CNPq/PPGACL/UFJF), the project explores the intersections of algorithmic design, listening practices, instrument-making, and critical pedagogy. The work proposes a reconceptualization of musical writing as an expanded gesture, where listening, space, and memory are deeply intertwined.